2017
DOI: 10.15616/bsl.2017.23.2.104
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Effects ofAster yomenaExtracts by the Suppression of Inducible Nitric Oxide Synthase Expression

Abstract: Inflammation is a pathophysiological process that is known to be involved in numerous diseases. Microbial infection or tissue injury activates inflammatory responses, resulting in the induction of proinflammatory proteins including inducible nitric oxide synthase (iNOS). Aster yomena is used in traditional Korean remedies. Here, we investigated the effects of ethanol extracts of Aster yomena (EAY) on the expression of iNOS induced by ovalbumin (OVA), one of the major egg allergens, or lipopolysaccharide (LPS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…On the contrary, treatment with EFAY down-regulated the expressions of IL-1β and COX-2. Earlier, it has been revealed that several phenolic compounds present in EFAY dysregulated interleukin-6 production in TNF-α stimulated MG-63 cells, proposing their role as anti-inflammatory agents [45]. Furthermore, EFAY lowered ovalbumin-and LPS-induced inflammation by down-regulating NF-κB and iNOS in RAW 264.7 cells [46].…”
Section: Discussionmentioning
confidence: 98%
“…On the contrary, treatment with EFAY down-regulated the expressions of IL-1β and COX-2. Earlier, it has been revealed that several phenolic compounds present in EFAY dysregulated interleukin-6 production in TNF-α stimulated MG-63 cells, proposing their role as anti-inflammatory agents [45]. Furthermore, EFAY lowered ovalbumin-and LPS-induced inflammation by down-regulating NF-κB and iNOS in RAW 264.7 cells [46].…”
Section: Discussionmentioning
confidence: 98%